Training on Using the Adobe Animate Application in Designing Learning Media for Junior High School Teacher - Wahyuni, Astri; Zafrullah, Zafrullah (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
The use of technology such as Adobe Animate has brought a lot of variety to education, increasing the way of delivering material that is more interactive and interesting for students. This provides significant benefits for many people in enhancing their learning experience. This service activity aims to provide training to teachers and simulations to students regarding Adobe Animate. The method of implementing this service involves lectures, practice and direct interaction with teachers and class VIII students at one of the State Middle Schools in West Bandung Regency. The training was carried out through demos, question and answer sessions, and simulations involving 5 class VIII students. The results of this service show that the teachers succeeded in understanding the concepts and techniques of using Adobe Animate in learning. Through the training and simulations carried out, they show progress in implementing this technology in daily learning activities. On the other hand, the simulation results also show positive changes in students, where they begin to show increased skills and confidence in following the learning process with Adobe Animate. This application not only provides benefits for teachers in delivering material interactively, but also provides a more interesting and effective learning experience for students.